Comparative efficacy of neoadjuvant therapy in the combined treatment of bladder cancer after open and transurethral resection - Dumansky, Y. V.; Maltsev, O. V. (Zaporozhye Medical Journal, 2013)
There are represented results of the use of different modes of neoadjuvantchemoradiation impact in the combined treatment of bladder cancer Ta-T2a stages after open and transurethral resection. The most effective was the scheme including endolymphaticpolychemotherapy which allowed in the performance of transurethral resection statistically significantly achieve 5-year survival rate and life expectancy 96,3±3,63% and 4,98±0,02 respectively.